Bioassay guided isolation and identification of the antioxidant constituent from Holostemma Ada-kodien shcult - JUNAPUDI SUNIL,; YASODHA KRISHNA JANAPATI,; PALLAVAL VEERA BRAMHACHARI, (International Journal of Pharma and Bio Sciences, 2017)
Holostemma ada-kodien shcult (Syn: Holostemma annulare) is a traditionally used in Indian herbal medicine. The objective of this study is to investigate the antioxidant activity of a bioassay-guided fractionation and its active components/compounds. Compounds were isolated by high performance thin layer chromatography (HPTLC) and preparative high performance liquid chromatography (pre-HPLC) and their structures were established by mass spectrometry (MS), Nuclear magnetic resonance (NMR) and fourier transform infrared spectroscopy (FT-IR) spectroscopic analyses. The antioxidant activity of ethyl acetate extract of Holostemma ada-kodien shcult and its fractions (CE, CF, EAF, MF and AF) were investigated using free radical scavenging activity, superoxide radical-scavenging assay, hydroxyl radical scavenging assay and assay of FeCl3 power. The results revealed that the antioxidant activity of different fractionations such as CE and EAF showed prominent activity when compared with butylated hydroxyltoluene (BHT) in a dose-dependent manner. Two compounds were isolated from Fraction –D among them quercetin and acacetin were reported for the first time in H. ada-kodien. Quercetin showed a more prominent antioxidant activity potential at concentrations (10, 20, 30, 40 and 50μg/mL) when compared with the other compounds. In conclusion the ethyl acetate fraction proved to have significant therapeutic potential for antioxidant effect.